Bipedicled digital artery perforator volar adiposal turned-over flap for reconstruction of transverse fingertip amputation. (June 2022) - Onode, Ema; Takamatsu, Kiyohito; Kazuki, Kenichi; Nakamura, Hiroaki
Summary: Different approaches to fingertip reconstructions are reported for cases in which microsurgical replantation is impossible. This report presents two cases of bipedicled digital artery perforator adiposal flaps for fingertip reconstruction after traumatic amputations. Adiposal flaps, including the radial and ulnar digital artery perforator vessels proximal to the distal interphalangeal joint, were elevated and turned to cover the fingertip defect. After donor-site skin closure, split-thickness skin was grafted onto the fingertip digital artery perforator adiposal flap. The technique is quick and easy to perform under loupe magnification and achieves good results in terms of healing, hand function, appearance, and patient satisfaction.